الوطن عند شعراء التجديد في المملكة العربية السعودية - آل حمادي، عبدالله بن أحمد بن حامد (جامعة الملك عبدالعزيز, 2015)
This study raises some central questions about the attitude of the modern poem towards the homeland: the Kingdom of Saudi Arabic. Firstly, has this poem followed the same vision that was recorded by the classical poetry? (Where the subject of glorifying the homeland comes at the beginning)? Secondly, has this poem taken another route, which is consistent with the development of new prospects of technical and semantic formation in poetry? In this study, there is a group of poets who sang to the homeland (Muhammad Hassan Awad, Ghazi al-Qusaibi, Muhammad alThubyti, Ali al- Dumayni, Abdullah al-Saikhan, Thurayyah alUrayyid, and Badia Kashgari) . So what did they say ? and what are their visions?
يطرح هذا البحث عدة أسئلة مركزية حول موقف القصيدة الحديثة من الوطن: المملكة العربية السعودية. وهذه الأسئلة هي: أولاً: هل سارت هذه القصيدة نحو الرؤية ذاتها التي سجلتها القصيدة التراثية من الوطن (حيث النغمة الاحتفالية الفخرية المعتزة)؟ ثانياً: هل اتخذت هذه القصيدة طريقاً آخر، يتواءم مع استحداث آفاق جديدة من التشكيل الفني والدلالي في الشعر؟ وفي هذه الدراسة توجد نخبة من الشعراء الذين ينشدون للوطن (محمد حسن عواد، غازي القصيبي، محمد الثبيتي، علي الدميني، عبد الله الصيخان، ثريا العريض، بديعة كشغري)، فماذا قالوا؟ وما هي رؤاهم؟
Keywords: الشعر السعودى -- الشعر الوطنى -- المواطنة -- الشعراء السعوديين -- السعودية